2016
DOI: 10.1089/jpm.2015.0341
|View full text |Cite
|
Sign up to set email alerts
|

Death in the Digital Age: A Systematic Review of Information and Communication Technologies in End-of-Life Care

Abstract: Background: End-of-life (EOL) communication plays a critical role in ensuring that patients receive care concordant with their wishes and experience high quality of life. As the baby boomer population ages, scalable models of end-of-life communication will be needed to ensure that patients receive appropriate care. Information and communication technologies (ICTs) may help address the needs of this generation; however, few resources exist to guide the use of ICTs in EOL care.Objective: The primary objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 82 publications
0
91
0
7
Order By: Relevance
“…In view of this, health education technologies, including educational video, are an attractive form of communication, since audio and video are capable of holding the attention of the viewer. The validation of expert content judges and technicians make these technologies effective and appropriate to the public, and may favor the modification of the health habits of a population, as it correctly informs, bringing it closer to its reality, in order to make it more adapted to the environment in which it is included (26) . Roy's Adaptation model states that the person adapts holistically, interacting with internal and external environments.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, health education technologies, including educational video, are an attractive form of communication, since audio and video are capable of holding the attention of the viewer. The validation of expert content judges and technicians make these technologies effective and appropriate to the public, and may favor the modification of the health habits of a population, as it correctly informs, bringing it closer to its reality, in order to make it more adapted to the environment in which it is included (26) . Roy's Adaptation model states that the person adapts holistically, interacting with internal and external environments.…”
Section: Discussionmentioning
confidence: 99%
“…33 These care models will depend on innovation in how ACP is provided. In their recent review of information and communication technologies in end-of-life care, Ostherr et al 34 concluded that scalable new technologies are "sorely needed to improve quality of life at the end-of-life while reducing costs of care." 34(p417) The risk factors associated with potentially avoidable terminal oncology ICU hospitalizations could potentially be used as a starting point to structure a precision algorithm to identify patients with cancer at high risk for avoidable aggressive end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on prevailing isolation/social distancing policies and resources, the NOK can conduct videoconferencing sessions in the hospital. 3 However, briefing must be done beforehand to prepare the NOK regarding the patient's condition and possibly how they appear visually. Additionally, the meeting must be supported by professional staff, with anticipation of psychoemotional outbursts.…”
Section: Communication Optionsmentioning
confidence: 99%
“…Alternatively, a call-in option may be considered. 3 Other options include prerecorded messages in the form of letters or audio recordings in conjunction with comfort objects, for example the patient's or NOK's treasured items can serve as a linking object for the patient and NOK. These items can be kept in the casket to signify a continuing bond between the patient and NOK.…”
Section: Communication Optionsmentioning
confidence: 99%